TAX FAIRNESS PERCEPTION AND TAX COMPLIANCE: STUDI EMPIRIK PADA WAJIB PAJAK ORANG PRIBADI KARYAWAN DI BANDUNG - Verani Carolina; Riana Fortunata (InFestasi, 2013)
This study aims to examine whether perceptions of tax fairness influence on salaried taxpayer compliance. Richardson (2006) indetify tax fairness as an issue that positively impact tax compliance in Hong Kong. Recent research reveal that tax knowledge affects the perception of tax fairness and finally affects Malaysian taxpayers compliance behaviour (Saad, 2010). This research was conducted by questionnaire survey method in salaried taxpayers in Bandung. Regression analysis was used to identify the research variables (tax fairness and tax compliance). The results showed that vertical tax fairness and horizontal tax fairness are significantly affect salaried taxpayers compliance in Bandung.